2008
DOI: 10.1017/s1068280500002173
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Exit and Entry of Farmers in a Crop Insurance Program

Abstract: This paper examines the factors influencing farmer participation in crop insurance schemes, but unlike previous studies that focus on total demand, participation is disaggregated into entrants and those exiting. Modeling entry and exit decisions separately illustrates that the effect of a given variable is often muted by aggregation. In addition, the approach in this paper distinguishes between price and yield variables rather than total returns and is consequently able to demonstrate that price variables are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Cabas et al . () model the entry and exit decisions using panel data consisting of the total number of insured and uninsured farmers at the county level. They find that insured farmers are more sensitive than uninsured farmers to changes in the preceding year's yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cabas et al . () model the entry and exit decisions using panel data consisting of the total number of insured and uninsured farmers at the county level. They find that insured farmers are more sensitive than uninsured farmers to changes in the preceding year's yield.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis conducted by Cabas et al . () aims at filling this gap. However, the authors analysed the phenomenon at an aggregate level, whereas we explicitly model farm‐level decisions of whether to adopt, enter or exit the insurance market.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 127 who indicated that they would not purchase insurance in 2012, 113 were not insured in 2011 either, but 14 were. Further research should examine what influences farmers' willingness to continue to take out insurance or not (Cabas et al, 2008). The development of the 344 AFR 74,3…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, regions with larger surface devoted to wheat production are considered as more crop specialized areas. Crop specialization, and thus lower income sources, increases farm revenue risk as farms become dependent on the performance of a single crop, becoming crop insurance an interesting alternative risk management tool (Cabas et al, 2008;Niewuwoudt et al, 1985).…”
Section: Wheat Insurance Demand Modelsmentioning
confidence: 99%